2019
DOI: 10.31234/osf.io/kcv3s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovering Bistable Systems from Psychological Time Series

Abstract: Conceptualizing mental disorders as complex dynamical systems has become a popular framework to study mental disorders. Especially bistable dynamical systems have received much attention, because their properties map well onto many characteristics of mental disorders. While these models were so far mostly used as stylized toy models, the recent surge in psychological time series data promises the ability to recover such models from data. In this paper we investigate how well popular (e.g., the Vector Autoregre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For practical reasons, variables are often measured within the same time-scale (usually once a day or every few hours), potentially leading to biased estimates in dynamical models. A recent simulation study suggests that using the most commonly applied ESM time-intervals results in data models that are largely unable to recover the micro dynamics of a system [49]. A stronger focus on theory and the utilization of clinical knowledge could therefore be helpful in informing relationships in the estimated model that cannot reasonably be captured by commonly used ESM data.…”
Section: The Role Of Computational Models In Bridging the Scientist-pmentioning
confidence: 99%
“…For practical reasons, variables are often measured within the same time-scale (usually once a day or every few hours), potentially leading to biased estimates in dynamical models. A recent simulation study suggests that using the most commonly applied ESM time-intervals results in data models that are largely unable to recover the micro dynamics of a system [49]. A stronger focus on theory and the utilization of clinical knowledge could therefore be helpful in informing relationships in the estimated model that cannot reasonably be captured by commonly used ESM data.…”
Section: The Role Of Computational Models In Bridging the Scientist-pmentioning
confidence: 99%
“…Data is simulated from the Panic Model, the full specification of which is given by (D. J. Robinaugh, Haslbeck, et al, 2019), using the statistical programming language R. We use the Panic Model to generate time-series data of 1000 individuals, on a single minute time scale, for 12 weeks, using Euler's method with a step size of .001. This yields a total of n t = 12, 0960 repeated measurements per person.…”
Section: A Simulated Data From the Panic Modelmentioning
confidence: 99%
“…Two variables that have a stable causal connection in a complex system may exhibit non-stationary correlation with each other, even to the point that the correlation coefficient switch signs [100]. In a simulation study on psychological dynamics, Haslbeck and Ryan [101] found that a VAR model cannot retrieve the complex systems model that generated the data. Sugihara et al [100] propose convergent cross mapping as a possible alternative for Granger causality.…”
Section: Scientific Implicationsmentioning
confidence: 99%